2016
DOI: 10.4172/2329-9096.1000372
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Plantar Fasciitis and Posterior Heel Pain: A Review

Abstract: This review focuses on the various techniques of conservative treatment of plantar fasciitis and posterior heel pain. Being the optimal therapy controversial, the intent is to drive surgeons and rehabilitation specialists in the choice of the strategies. The Data sources were MEDLINE, PubMed, CINAHL, EMBASE, and Psych INFO databases using the selected key words. Studies have been selected for review using as criteria English, adults, clinical population and intervention. Among several published studies about r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Ultrasound-guided PNE was effective in the short term (0-3 months) and the intermediate term (3-6 months), providing better pain relief and improvement of functional disability than placebo. The latest published reviews on CPHP treatment include evidence for the benefits of manual therapy, stretching, taping, foot orthoses, and night splints 5,7,24,28 ; furthermore, there is weak evidence for the efficacy of low-level laser therapy and phonophoresis with ketoprofen gel, and conflicting evidence for electrotherapy with 0.4% dexamethasone or 5% acetic acid delivered via iontophoresis, acupuncture, or trigger point dry needling. 5,7,24,28 The Cochrane Review concluded that there is low quality evidence for short-term pain relief following corticosteroid injection (CI) with placebo or no treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound-guided PNE was effective in the short term (0-3 months) and the intermediate term (3-6 months), providing better pain relief and improvement of functional disability than placebo. The latest published reviews on CPHP treatment include evidence for the benefits of manual therapy, stretching, taping, foot orthoses, and night splints 5,7,24,28 ; furthermore, there is weak evidence for the efficacy of low-level laser therapy and phonophoresis with ketoprofen gel, and conflicting evidence for electrotherapy with 0.4% dexamethasone or 5% acetic acid delivered via iontophoresis, acupuncture, or trigger point dry needling. 5,7,24,28 The Cochrane Review concluded that there is low quality evidence for short-term pain relief following corticosteroid injection (CI) with placebo or no treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The latest published reviews on CPHP treatment include evidence for the benefits of manual therapy, stretching, taping, foot orthoses, and night splints 5,7,24,28 ; furthermore, there is weak evidence for the efficacy of low-level laser therapy and phonophoresis with ketoprofen gel, and conflicting evidence for electrotherapy with 0.4% dexamethasone or 5% acetic acid delivered via iontophoresis, acupuncture, or trigger point dry needling. 5,7,24,28 The Cochrane Review concluded that there is low quality evidence for short-term pain relief following corticosteroid injection (CI) with placebo or no treatment. 12 A recent review by Tsikopoulos et al 36 reported that micronized dehydrated human amniotic/chorionic membrane (mDHACM) is the best injection option in the short term, and botulinum toxin A is the most likely to relieve pain intensity in the first 0 to 6 months after treatment.…”
Section: Discussionmentioning
confidence: 99%